2011
DOI: 10.1002/j.2161-007x.2011.tb01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Death Education and Attitudes of Counselors‐in‐Training Toward Death: An Exploratory Study

Abstract: This study reviewed how attitudes of counselors-in-training toward death develop after completing a course on death education. Participants included 11 graduate counseling students enrolled in a 2-credit-hour course addressing death and dying, and grief and loss. Qualitative results from a content analysis of free-response narratives suggest the emergence of 3 themes: openness to examining death and death constructs; increased understanding of death; and reduced negative emotional state, namely, fear of death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 28 publications
1
22
0
5
Order By: Relevance
“…Por esta razón, el cambio debe originarse como consecuencia natural de un proceso formativo necesario y profundo en este ámbito para la preparación de los futuros profesionales de la educación. Ya se han implementado programas para profesionales de la educación sobre la muerte que se han desarrollado internacionalmente (Harrawood, Doughty y Wilde, 2011), cuyos resultados apuntan a que dicho proceso formativo favoreció la comprensión sobre la finitud y la mortalidad del ser humano, a la par que redujo la ansiedad ante la muerte. Este aspecto es importante de considerar, ya que existe una relación significativa entre el grado de reflexión y conocimiento de los profesores sobre la muerte y su actitud favorable a la normalización educativa de la misma (Herrán y Cortina, 2006).…”
Section: Discusión Y Conclusionesunclassified
“…Por esta razón, el cambio debe originarse como consecuencia natural de un proceso formativo necesario y profundo en este ámbito para la preparación de los futuros profesionales de la educación. Ya se han implementado programas para profesionales de la educación sobre la muerte que se han desarrollado internacionalmente (Harrawood, Doughty y Wilde, 2011), cuyos resultados apuntan a que dicho proceso formativo favoreció la comprensión sobre la finitud y la mortalidad del ser humano, a la par que redujo la ansiedad ante la muerte. Este aspecto es importante de considerar, ya que existe una relación significativa entre el grado de reflexión y conocimiento de los profesores sobre la muerte y su actitud favorable a la normalización educativa de la misma (Herrán y Cortina, 2006).…”
Section: Discusión Y Conclusionesunclassified
“…Further, beginning counselors report greater distress associated with death and dying than other clinical situations (Kirchberg & Neimeyer, 1991). Narratives of counselors in training indicated that a 2-credit course on death education provided enhanced openness to thinking about and discussing death, greater awareness of personal death attitudes, and decreased negative affect related to death (Harrawood et al, 2011). Harrawood et al called for (a) additional research on counselors' self-knowledge about death and openness to thanatological content, and (b) inclusion of grief and loss in accreditation DEATH EDUCATION AND COUNSELOR PREPARATION standards.…”
Section: Service-learning Graduate Education Counselor Preparationmentioning
confidence: 99%
“…Even when counselors in training do not specialize in death and dying, they cannot avoid working with dying or grieving individuals during their careers. An ongoing challenge is balancing accreditation standards (e.g., Council on Social Work Education [CSWE], Council for Accreditation of Counseling & Related Educational Programs [CACREP], and American Psychological Association Commission on Accreditation [APA CoA]) with critical curricular content areas such as death and dying (e.g., Harrawood, Doughty, & Wilde, 2011).…”
mentioning
confidence: 99%
“…More research is needed to guide instructors on how to successfully implement assignments that will achieve positive learning outcomes for students. Furthermore, many prior studies focused on assignments that supported individuals who were actively grieving loss from death (Doll et al, 2008) or to specifically prepare students to work in healthcare (Berzoff et al, 2005;Gould, 1994;Harrawood, Doughty, & Wilde, 2011;Konrad, 2010). We argue that death education courses can benefit most students (beyond those seeking work in health care or social sciences) and can prepare individuals who are not currently grieving for inevitable future encounters with bereavement, grief, and loss in their personal and professional lives.…”
mentioning
confidence: 97%